2007
DOI: 10.1097/wnr.0b013e32811d6d21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tobacco and cigarette smoke extracts on serotonergic raphe neurons in the rat

Abstract: Tobacco components other than nicotine might participate in the behavioural effects of smoking. In this study, in-vivo recordings of serotonergic dorsal raphe neurons were performed in the anesthetized rat, whereas tobacco extracts, cigarette smoke extracts, nicotine, nornicotine or anabasine were intravenously injected. All substances inhibited the neurons, and all inhibitions were completely blocked by the nicotine receptor antagonist mecamylamine. The effects of the extracts were much more potent than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Such an effect may help explain the discrepancy between nicotine and tobacco extract effects observed in vitro (see Ambrose et al 2007 ;Touiki et al 2007), but has yet to be investigated in respect of the other minor tobacco alkaloids.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such an effect may help explain the discrepancy between nicotine and tobacco extract effects observed in vitro (see Ambrose et al 2007 ;Touiki et al 2007), but has yet to be investigated in respect of the other minor tobacco alkaloids.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, a tobacco extract containing all minor alkaloids produces greater nAChR-mediated inhibition of serotonergic neurons than nicotine alone, with nornicotine, anabasine and nicotine individually producing similar levels of inhibition (Touiki et al 2007). Furthermore, anabasine, cotinine, and nornicotine also elicit a calcium-dependent increase in striatal dopamine release through activation of the nAChR, and similarly to nicotine, produce nAChR desensitization (Dwoskin et al 1995 ;O'Leary et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…CRF, endogenous opioids, and orexins). For details on the relevance of these diverse actions of NIC in various brain functions and in the development and maintenance of NIC dependence, (see De Biasi and Salas, 2008;Di Matteo et al, 2007;Touiki et al, 2007Touiki et al, , 2008Seth et al, 2002;Galindo-Charles et al, 2008;Rossi et al, 2005a,b;Grilli et al, 2005;Markou, 2007Markou, , 2008Liechti and Markou, 2008;Kenny et al, 2009;Hahn and Stolerman, 2005;Erhardt et al, 2000;George et al, 2007;Xue and Domino, 2008;Chen et al, 2008b;Merritt et al, 2008;Pasumarthi and Fadel, 2008).…”
Section: Relevance Of Dopamine In Nicotine Addictionmentioning
confidence: 98%
“…Particulate matter, derived from an ethanol extract of tobacco, produces similar effects to nicotine on locomotor activity (Brennan et al, 2013). Smoke extract, which contains many combustion products not present in tobacco leaf (Bates et al, 1999;Seeman et al, 2002), has been shown to have in vitro effects on dopamine neurons that are distinct from those of tobacco extract (Marti et al, 2011) and on serotonin neurons that are distinct from those of nicotine (Touiki et al, 2007). However, to date, there have been no studies of the behaviorally reinforcing effects of tobacco smoke extracts.…”
Section: Introductionmentioning
confidence: 99%